Criminalité organisée dans la région arabe - Kahi, Mabrouk (Journal of Human Sciences, 2021)
The topic of the study deals with the phenomenon of organized crime in the Arab region, this phenomenon that has been widely spread recently within the Arab regional system, taking advantage of the available conditions such as the security law that some Arab countries know, and the spread of administrative corruption that is eating away at the structure of the torn country itself, as well as The study refers to the geostrategic situation of the Arab. The study is divided into two main axes. The first includes the inherent aspect of organized crime, from basic definitions and concepts as well, characteristics and pillars of organized crime. As for the second axis, it was related to organized crime in the Arab region, the reasons for the spread of this serious pest, as well as its forms and manifestations in the Arab region and trying to compare it with what is It exists in the world, and the third component of the first axis is related to mechanisms to combat organized crime in the Arab region.